Heat and work integration: Fundamental insights and applications to carbon dioxide capture processes. (1st August 2016) - Fu, Chao; Gundersen, Truls
Graphical abstract: Highlights: The problem definition of heat and work integration is introduced. The fundamental insights of heat and work integration are presented. The design methodology is illustrated with two small test examples. Applications of to three carbon dioxide capture processes are presented. Abstract: The integration of heat has achieved a notable success in the past decades. Pinch Analysis is a well-established methodology for heat integration. Work is an equally important thermodynamic parameter. The enthalpy of a process stream can be changed by the transfer of heat and/or work. Heat and work are actually interchangeable and can thus be integrated. For example, compression processes consume more work at higher temperatures, however, the compression heat may be upgraded and utilized; expansion processes produce more work at higher temperatures, however, more heat may be required. The classical heat integration problem is thus extended to a new research topic about the integration of both heat and work. The aim of this paper is to present the problem definition, fundamental thermodynamic insights and industrial applications of heat and work integration. The results from studies on the three carbon dioxide capture processes show that significant energy savings can be achieved by proper heat and work integration. In the oxy-combustion process, the work consumption for cryogenic air separation is reduced by 10.1%. In the post-combustion membrane separation process, the specific work consumption for carbon dioxide separation is reduced by 12.9%. In the membrane air separation process, the net work consumption (excluding heat consumption) is reduced by 90%.